Using service learning instructional strategy in teaching social studies for improving students’ creativity skills and reducing unemployment (2019)
This study examined effect of service learning instructional strategy on students’ creativity skill. Three hypotheses were formulated and tested at 0.05 level of significance. The study adopted the pretest-posttest control group quasi experimental design Two local government areas, which include Ibadan North and Akinyele local government were randomly selected from five local government in Ibadan metropolis while two schools were purposively selected in each of the local government. The participant were JSS1 students and a total number of 230 (131 female and 99 male) participants were used. Three validated instruments were used for the study. Namely, Student Creative Skill Scale (r= 0.71); Teachers Instructional Guide for Conventional Strategy and Service Learning Guide. Data collected were analysed using Analysis of Covariance. There was a significant main effect of treatment on students’ creative skill (F (1,219) = 6.166; p<0.05, partial η2 = 0.027). There was no significant main effect of gender on students’ creative skill There was no significant two-way interaction effect of treatment and gender on students’ creative skill (F (1,219) = 0.083, p>0.05, partial η2 = 0.000). It was therefore concluded that service Learning Strategy enhanced student acquisition of creative skill through entrepreneurial related topics in Social Studies. Social studies teachers should adopt this strategy when teaching entrepreneurial related topics.